Effect of Bay Leaf (Syzygium polyanthum) Extract on Antioxidant Activity, MDA Levels, and Liver Histopathology Feature of Ethambutol Induced Wistar Rats - Bambang Edi Suwito; Lea Maera Shanty; Retna Gumilang; Handayani Handayani; Renata Alya Ulhaq (Universitas Nahdlatul Ulama Surabaya, 2022)
Bay leaf extract (Syzygiun polianthum) is one herbal elemnt that may be used to lessen liver function issues, lessen symptops of nausea, vomiting, discomfort and improve adherence and the effectiveness of tuberculossi treatment. The objective of this study was to determine the effect of bay leaf (Syzygium polyanthum) extract on antioxidant activity, Malondialdehyde (MDA) levels, and liver histopathology of ethambutol-induced Wistar rats. This research is a laboratory experiment. Antioxidant activity of Bay Leaf Extract was evaluated by comparing vitamin C with spectrophotometry methods. White Wistar rats were separated into 6 groups and uset to test the lebel of MDA and livers histopathology. Group 1 serves as the control group and received DMSO (placebo); Group 2 was received ethambutol 50mg/kg BW; Group 3 was received ethambutol and silymarine with dose 50mh/kg BW. Group 4-6 had been given ethambutol and extra ethanol extract of bay leaves of 75,150, dan 300mg/kg BW, respectively. The results of the spectrophotometry showed that the Bay Leaf Extract had antioxidant activity comparable to that of vitamin C, with an IC50 of 11.4 g ± (4.4%). One-Way ANOVA test results obtained p = 0.002 (p<0.05) while the Kruskal-Wallis test results obtained the Asymp. Sig value 0.105> 0.05. There was a significance difference in each group’s MDA levels (p=0.002). Although there was no significant difference in the liver histopathology of treated rats (p>0.05). While bay leaf extract significantly lowers MDA levels in ethambutol-induced Wistar rats, it has no discernible impact on the liver histopathology of ethambutol-induced Wistar rats. Bay leaf extract possesses antioxidant activity comparable to vitamin C.